Effect of System Contaminants on the Performance of a Proton Exchange Membrane Fuel Cell. Issue 14 (10th November 2016) - Mehrabadi, Bahareh Alsadat Tavakoli; Dinh, Huyen N.; Bender, Guido; Weidner, John W.
Abstract : The performance loss and recovery of the fuel cell due to Balance of Plant (BOP) contaminants was identified via a combination of experimental data and a mathematical model. The experiments were designed to study the influence of organic contaminants (e.g. those from BOP materials) on the resistance of the catalyst, ionomer and membrane, and a mathematical model was developed that allowed us to separate these competing resistances from the data collected on an operating fuel cell. For this reason, based on the functional groups, four organic contaminants found in BOP materials, diethylene glycol monoethyl ether (DGMEE), diethylene glycol monoethyl ether acetate (DGMEA), benzyl alcohol (BzOH) and 2, 6-diaminotoluene (2, 6-DAT) were infused separately to the cathode side of the fuel cell. The cell voltage and high frequency impedance resistance was measured as a function of time. The contaminant feed was then discontinued and voltage recovery was measured. It was determined that compounds with ion exchange properties like 2, 6-DAT can cause voltage loss with non-reversible recovery, so this compound was studied in more detail. The degree of voltage loss increased with an increase in concentration, and/or infusion time, and increased with a decrease in catalyst loadings.